2013
DOI: 10.5194/acp-13-1733-2013
|View full text |Cite
|
Sign up to set email alerts
|

A numerical study of aerosol influence on mixed-phase stratiform clouds through modulation of the liquid phase

Abstract: Numerical simulations were carried out in a high-resolution two-dimensional framework to increase our understanding of aerosol indirect effects in mixed-phase stratiform clouds. Aerosol characteristics explored include insoluble particle type, soluble mass fraction, influence of aerosol-induced freezing point depression and influence of aerosol number concentration. Simulations were analyzed with a focus on the processes related to liquid phase microphysics, and ice formation was limited to droplet freezing. O… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…The same "high CCN" and "low CCN" cases, with the same initial conditions, were run with different criteria for heterogeneous freezing. Assuming freezing can only occur above water saturation, as in previous studies by de Boer et al (2010) and as observed by Ansmann et al (2008), shows no suppression of ice formation. The number concentration of ice in the "high CCN" and "low CCN" cases is the same.…”
Section: Demonstration Of the Suppression Effectsupporting
confidence: 61%
See 4 more Smart Citations
“…The same "high CCN" and "low CCN" cases, with the same initial conditions, were run with different criteria for heterogeneous freezing. Assuming freezing can only occur above water saturation, as in previous studies by de Boer et al (2010) and as observed by Ansmann et al (2008), shows no suppression of ice formation. The number concentration of ice in the "high CCN" and "low CCN" cases is the same.…”
Section: Demonstration Of the Suppression Effectsupporting
confidence: 61%
“…However their explanation of this effect differs from the one put forward here. de Boer et al (2013) explain that the reduction in ice formation in their simulations performed with high CCN concentrations is due to a reduction in drop vol-ume, similar to the Twomey effect (Twomey, 1974). The immersion freezing parameterisation that de Boer employ is a function of drop volume and the production of ice particles through immersion freezing decreases as drop volume decreases.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations